2017
DOI: 10.1038/cddis.2017.402
|View full text |Cite
|
Sign up to set email alerts
|

Novel chimeric transcript RRM2-c2orf48 promotes metastasis in nasopharyngeal carcinoma

Abstract: Recently, chimeric transcripts have been found to be associated with the pathogenesis and poor prognosis of malignant tumors. Through our preliminary experiment, a novel chimeric transcript called chimeric transcript RRM2-c2orf48 was detected in C666-1, a classical cell line of human nasopharyngeal carcinoma (NPC). Therefore, the objective of this study was to demonstrate the existence and expression of novel chimeric transcript RRM2-c2orf48 and to explore the main functions and mechanisms of RRM2-c2orf48 in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Immunofluorescence analysis was performed as described previously [23]. The samples were incubated overnight at 4 °C with primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence analysis was performed as described previously [23]. The samples were incubated overnight at 4 °C with primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al constructed a ceRNA regulatory network for oral squamous cell carcinoma, and showed that 6 lncRNAs, including C2orf48, were associated with overall cancer survival [30]. Another study showed that C2orf48 could bind to RRM2 to form a chimeric transcript and high expression of RRM2-C2orf48 increased migration and invasion of nasopharyngeal carcinoma cells [31]. The role of C2orf48 in endometrial carcinoma has not been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher adrenocortical cancer [8], lung cancer [9], nasopharyngeal cancer [10], gastric cancer [11] and neuroblastoma [12], as well as being a predictor of poor prognosis [13][14][15][16][17]. Our previous study had indicated that RRM2 plays a critical role in the diagnosis and treatment of cervical cancer [18].…”
Section: Ivyspringmentioning
confidence: 99%
“…RRM2, as a component of ribonucleotide reductase (RNR), plays vital roles in many critical cellular processes such as cell proliferation, invasiveness, migration, angiogenesis and senescence 7 . It is frequently overexpressed and serves as an oncogene in various malignancies, including adrenocortical cancer 8 , lung cancer 9 , nasopharyngeal cancer 10 , gastric cancer 11 and neuroblastoma 12 , as well as being a predictor of poor prognosis 13 - 17 . Our previous study had indicated that RRM2 plays a critical role in the diagnosis and treatment of cervical cancer 18 .…”
Section: Introductionmentioning
confidence: 99%